Six Early Printed Maps [Material cartográfico]: selected from those exhibited at the British Museum on the occasion of the International Geographical Congress. - British Museum (Printed by order of the Trustees, 1928)
Incluye mapas de Europa central, las Islas Británicas, Mundo, la región del Atlántico norte, el territorio Mogul y el este de Estados Unidos. Mapas datados 1492-1655 Tabla de contenidos en inglés, mapas en alemán y en latín Copia digital. Madrid : Ministerio de Cultura. Dirección General del Libro, Archivos y Bibliotecas, 2010 1: Das ist der Rom-Weg von Meylen zu Meylen mit Puncten verzeychnet von eyner Stat zu der andern durch deutzsche Lantt / [by Erhard Etzlaub]. Nuremberg, ca. 1492 2: Britanniae insulae quae nunc Angliae et Scotiae regna continet cum Hibernia adiacente nova descriptio / [by George Lily]. Romae, 1546 3: Nova orbis terrarum descriptio optie proiecta / per Ioannem Blagravum. London, 1596 4: Nova Francia / [by Gabriel Tatton. London, ca. 1610 -- 5: A description of East India conteyninge th' Empire of the Great Mogoll / William Baffin deliniauit; Renold Elstrack sculp. London: T. Sterne, 1619 6: Novi Belgii novaeque Angliae nec non partis Virginiae tabula multis in locis emendata a N.J. Visschero. Amsterdam, ca. 1655.